The Implementation of IMC Tools on Marketing Communication in Niche Market @kedaionyi During Covid-19 Pandemic - Andariesta Adhani Panggita (MediaTor (Jurnal Komunikasi), 2021)
Covid-19 pandemic has been for almost two years. However, this pandemic is also turning the business flow into an online business, including Mataram city. Various type of online businesses has helped people to support their needs during the Covid-19 pandemic. One of them is Kedai Onyi, the niche market type in food catering with a low budget. The owners offer and develop the business on social media. The purpose of this research is to analyze and describe the implementation of online marketing communication used by the owner of Kedai Onyi based on the Integrated Marketing Communication (IMC) tools concept. This research is qualitative research with a descriptive method. The result of this research shows us that Kedai Onyi has implemented several IMC tools on its online business. But, the implementation is still not applied to the maximum level.